Analisa Pengaruh Penggunaan Oli Pelumas 15W-40 dan 10W-40 Terhadap Performa Mesin Motor Matic 110 CC - Mudzakir, M.; Ardian, Dedy Rachman; Sundari, Putri (Politeknik Negeri Padang, 2025)
This study aims to analyze the impact of using lubricating oils with SAE 10W-40 and SAE 15W-40 viscosities on the performance of 110cc automatic motorcycle engines. The tests focus on the effects of both types of oil on engine power, torque, and air-fuel ratio (Air Fuel Ratio/AFR). This research employs an experimental method involving laboratory tests and road tests to obtain accurate data. The viscosity tests show that SAE 10W-40 oil has lower viscosity at low and medium temperatures compared to SAE 15W-40, which has higher viscosity and is more stable at high temperatures. The power and torque tests indicate that SAE 10W-40 oil produces more stable maximum power within the medium RPM range, while SAE 15W-40 has a sharper peak power but within a more limited RPM range. The torque tests also show that SAE 10W-40 performs better in maintaining torque over a longer range. Additionally, AFR analysis indicates that SAE 10W-40 oil approaches the ideal ratio for efficient combustion, while SAE 15W-40 tends to produce a richer mixture at high RPM, which improves performance but reduces fuel efficiency. The results suggest that the selection of oil with the appropriate viscosity significantly affects engine performance, especially in terms of fuel efficiency, power, and torque in a 110cc automatic motorcycle.